Early Blood Transfusion After Kidney Transplantation Does Not Lead to dnDSA Development: The BloodIm Study - Thomas Jouve; Thomas Jouve; Johan Noble; Johan Noble; Hamza Naciri-Bennani; Céline Dard; Dominique Masson; Gaëlle Fiard; Gaëlle Fiard; Paolo Malvezzi; Lionel Rostaing; Lionel Rostaing (Frontiers in Immunology, 2022)
Outcomes after kidney transplantation are largely driven by the development of de novo donor-specific antibodies (dnDSA), which may be triggered by blood transfusion. In this single-center study, we investigated the link between early blood transfusion and dnDSA development in a mainly anti-thymocyte globulin (ATG)-induced kidney-transplant cohort. We retrospectively included all recipients of a kidney transplant performed between 2004 and 2015, provided they had >3 months graft survival. DSA screening was evaluated with a Luminex assay (Immucor). Early blood transfusion (EBT) was defined as the transfusion of at least one red blood-cell unit over the first 3 months post-transplantation, with an exhaustive report of transfusion. Patients received either anti-thymocyte globulins (ATG) or basiliximab induction, plus tacrolimus and mycophenolic acid maintenance immunosuppression. A total of 1088 patients received a transplant between 2004 and 2015 in our center, of which 981 satisfied our inclusion criteria. EBT was required for 292 patients (29.7%). Most patients received ATG induction (86.1%); the others received basiliximab induction (13.4%). dnDSA-free graft survival (dnDSA-GS) at 1-year post-transplantation was similar between EBT+ (2.4%) and EBT- (3.0%) patients (chi-squared p=0.73). There was no significant association between EBT and dnDSA-GS (univariate Cox’s regression, HR=0.88, p=0.556). In multivariate Cox’s regression, adjusting for potential confounders (showing a univariate association with dnDSA development), early transfusion remained not associated with dnDSA-GS (HR 0.76, p=0.449). However, dnDSA-GS was associated with pretransplantation HLA sensitization (HR=2.25, p=0.004), hemoglobin >10 g/dL (HR=0.39, p=0.029) and the number of HLA mismatches (HR=1.26, p=0.05). Recipient’s age, tacrolimus and mycophenolic-acid exposures, and graft rank were not associated with dnDSA-GS. Early blood transfusion did not induce dnDSAs in our cohort of ATG-induced patients, but low hemoglobin level was associated with dnDSAs-GS. This suggests a protective effect of ATG induction therapy on preventing dnDSA development at an initial stage post-transplantation.